KEDUDUKAN HAK PESERO KOMANDITER SEBAGAI SALAH SATU AHLI WARIS DARI PESERO KOMPLEMENTER TERHADAP ASET PERSEROAN KOMANDITER (CV) BERHADAPAN DENGAN HAK AHLI WARIS LAINNYA (STUDI KASUS PUTUSAN PK NOMOR 621PK/PDT/2015) - PENNI MARIANI PURBA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Notaris Dr. Suprayitno, SH, MKn To inherit is to take over a deceased’s right and obligation. The whole wealth (asset and liability) is automatically transferred from a testator to his heirs which is called saisine in heritage law starting from the testator’s death. The inheritance, i.e. the business profit from CV SEJAHTERA is one property of the estates bequeathed by the testator to his heirs (the plaintiff and defendant). The defendant is one of the partners of the CV established by their Parents who are the testator and complementary partners of CV SEJAHTERA at a time. The Ruling pronounced by the Judge to the Judicial Review is that the profit of the CV of IDR 2,000,000,000.00 (two billion rupiahs) shall be equally distributed to each heir, without considering its position (as one of the heirs) who is rightful over the profit.CV established by parents with one of their children acting as the CV partner causes wealth merging, so that if it is related to the inheritance distribution of the CV partner, it will not proportional because his position is equalized with the other heirs who do not take part in the company operation. It is suggested that the Articles of Association of the company be clearly emphasized about the capital invested by each partner so that in case of any dispute in the future, what is their right becomes obvious. It is also suggested that the Notary provide counseling to every person appearing in order to anticipate any problems in the future, particularly concerning inheritance of a CV established by parents whose child officiates as the CV partner.Keywords: CV Partner, Inheritance, Limited Partnership.